Trends in the top ten popular dog breeds in Serbia (2008-2022) - Janjić Filip; Živanović Dragana; Radaković Milena; Davitkov Dajana; Spariosu Kristina; Francuski-Andrić Jelena; Kovačević-Filipović Milica (Veterinarski Glasnik)
Information on the prevalence of the most popular breeds within one society can provide insights into its sociological, economic, and anthropological aspects, while also aiding in the organization of more effective veterinary services and improving animal welfare. This research aimed to determine whether there has been a change in dog breed ownership between the Serbian capital city, Belgrade (BG), and non-Belgrade (non-BG) regions over the last 15 years, for three five-year periods: 2008–2012, 2013– 2017, and 2018–2022. Data on breed prevalence were collected from the official Vetup database of the Republic of Serbia. Mixed-breed dogs were the most prevalent in both BG and non-BG regions across all three periods, though their percentage has declined in the most recent period relative to purebred dogs. In the first period, large working/ guardian breeds dominated in all regions. German Shepherds consistently ranked as the most prevalent purebred dogs across all periods and regions. In contrast, Maltese dogs emerged as the most prevalent breed in Belgrade during the two most recent periods. In 2013–2017, other small breeds began to emerge, and in the third period, they dominated the BG region, while larger breeds remained more common in non- BG regions. These changes may reflect lifestyle changes and urban preferences for smaller breeds better suited to apartment living. These trends reflect dog ownership preferences, shaped by lifestyle changes and socio-economic factors in urban and rural areas, while also aligning with global patterns but probably retaining unique traits of local patterns.